Variaciones en las capacidades estructurales self - otro de una mujer heterosexual violentada por su pareja en un contexto de psicoterapia psicoanalítica breve - Bullón Muñoz, Daniela del Carmen (2024)
Intimate partner violence in heterosexual relationships (IPVH) is a multifaceted issue that causes profound disruptions in the victims' psychic structure. These disruptions can manifest in difficulties in establishing healthy interpersonal relationships and differentiating between self and others. Psychotherapeutic treatment from a psychoanalytic perspective can provide a significant avenue for recovery and psychic reorganization. In this context, Interpersonal Dynamic Therapy (IDT) (Lemma et al., 2011) is a brief and focused intervention model that specifically addresses interpersonal dynamics and internal representations of significant relationships. However, empirical evidence on its effectiveness in cases of IPVH is still limited. This research aimed to contribute to the field of brief psychoanalytic psychotherapy by providing empirical evidence on its impact on the structural capacities of victims. A systematic single-case design was used to examine the initial and final phases of the IDT intervention. Representations of self and others were collected using the Core Conflictual Relationship Theme (CCRT) (Luborsky & Crits-Christoph, 1990), and its later reformulation translated into Spanish CCRT-LU-S (Espinosa & Valdés, 201 Finally, variations between phases were analyzed using Axis IV of the Operationalized Psychodynamic Diagnostics OPD II multiaxial system (OPD Task Force, 2008). The results showed that, although there was variation only in the capacity for external bonds, other capacities maintained a medium level of integration, showing variations when subcapacities were examined. The changes are discussed in the context of the 12-session work, considering the cultural and idiosyncratic context of the client and/or potential limitations of this work.